Variasi Geografik Kelimpahan Zooplankton di Perairan Terganggu, Kepulauan Seribu, Indonesia - Elok Faiqoh; Inna Puspa Ayu; Beginer Subhan; Yuliana Fitri Syamsuni; Aji Wahyu Anggoro; Andrianus Sembiring (Fakultas Kelautan dan Perikanan Universitas Udayana, 2015)
Zooplankton play a significant role in ecosystem as secondary producer. Climate change will potentially affect the abundance and global composition of zooplankton. This research aimed to study the geographical variation of zooplankton abundance relative to anthropogenic pressure. The research was conducted in April 2014 in area with presumably distinct anthropogenic level by its relative distance to the mainland of Jakarta. Samples were collected at Pramuka Island, Karang Beras Island, Kotok Island, and Sepa Island where subsequently lying to the nearest until furthest distance from mainland. Zooplankton samples were collected by towing the plankton net for 10 minutes for each site for three replicates. Abundance was obtained from Pramuka Island was 266698,214 ind/L, Karang Beras Island was 597363,1 ind/L, Kotok Island was 526447,8 ind/L and Sepa Island was 438225,3 ind/L. Overall, the closer to mainland, the richer nutrient and the more abundant zooplankton was conceived in the waters. Surprisingly, in Pramuka Island, the nearest island to mainland among other sites, had the lowest abundance of zooplankton although nutrient level was the richest among others.